Improving the Pharmacovigilance System in Medical Organisations as an Opportunity to Enhance the Quality of Pharmacotherapy - M. V. Zhuravleva; S. Yu. Serebrova; E. V. Kuznetsova; T. R. Kameneva; A. V. Vlasova; A. B. Prokofiev; E. Yu. Demchenkova (Безопасность и риск фармакотерапии, 2025)
INTRODUCTION. It is essential to monitor the efficacy and safety of medicinal products as part of post-marketing surveillance to identify, assess, and prevent adverse drug reactions (ADRs). The effectiveness of pharmacovigilance depends largely on healthcare professionals’ adherence to the requirements and timeframes for reporting information to regulatory authorities.AIM. This study aimed to identify and systematise the key aspects of pharmacovigilance through an analysis of experience in organising pharmacovigilance in Moscow-based healthcare institutions in 2018–2024 to determine the focus areas for implementing, monitoring, and improving the pharmacovigilance system operating in medical organisations.DISCUSSION. The significance of pharmacovigilance systems and the need for their continuous improvement are underpinned by experience in establishing pharmacovigilance databases, including the global VigiBase database, the European Union’s EudraVigilance database, and the Eurasian Economic Union’s database. The main pharmacovigilance tools include active surveillance and collection of unsolicited/solicited reports of suspected ADRs. The Russian Federal Service for Surveillance in Healthcare (Roszdravnadzor) has developed clear operational criteria for pharmacovigilance in medical organisations. These criteria require that medical organisations should have in-house regulations for collecting, registering, and reporting data on ADRs to Roszdravnadzor, appointing qualified persons responsible for pharmacovigilance, and obtaining access to the Pharmacovigilance database of Roszdravnadzor’s Automated Information System. This article provides a detailed description of tools for establishing an effective pharmacovigilance system in a medical organisation, as well as the focus areas for organising pharmacovigilance in medical organisations, identified by analysing the experience of a territorial entity of the Russian Federation.CONCLUSIONS. To improve the effectiveness of pharmacovigilance in medical organisations, it is necessary to ensure the quality, integrity, and completeness of data submitted in spontaneous ADR reports. Spontaneous reporting should be supplemented with active surveillance methods, including the Global Trigger Tool. The current pharmacovigilance system in Moscow demonstrates a steady increase in reporting ADRs to Roszdravnadzor.